2004
DOI: 10.1021/jo049501j
|View full text |Cite
|
Sign up to set email alerts
|

C−O Bond Fragmentation of 4-Picolyl- and N-Methyl-4-picolinium Esters Triggered by Photochemical Electron Transfer

Abstract: Photochemical reduction of several 4-picolyl- and N-methyl-4-picolinium esters was examined using product analysis, laser flash photolysis, and fluorescence quenching. It is demonstrated that the radical (anions) formed in these reactions readily fragment to yield a carboxylic acid and a 4-pyridylmethyl radical intermediate. The high chemical and quantum yields observed for these photoreactions suggests that these esters can be used as photolabile protecting groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 34 publications
2
44
0
Order By: Relevance
“…Cyclic voltammograms (see Supporting Information) showed irreversible redox processes for all six substrates, 7 – 12 . The first reduction potential was observed between E red =−1.09 V and E red =−1.37 V, with E red =−1.11 V for 7 which is very close to the reported E red =−1.08 V value measured for the corresponding perchlorate salt . Compounds 7 , 8 and 11 , 12 (i.e.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Cyclic voltammograms (see Supporting Information) showed irreversible redox processes for all six substrates, 7 – 12 . The first reduction potential was observed between E red =−1.09 V and E red =−1.37 V, with E red =−1.11 V for 7 which is very close to the reported E red =−1.08 V value measured for the corresponding perchlorate salt . Compounds 7 , 8 and 11 , 12 (i.e.…”
Section: Resultssupporting
confidence: 85%
“…Although sensitized probes, in which the light‐harvesting and working elements are functionally disconnected, allow considerably larger flexibility in the optimization process, somewhat surprisingly only modest interest has been paid for the development of such probes . Redox‐gated systems are among those, developed essentially around the 4‐picolyl family . The reduction potentials of the parent phenacyl ( E red =−2.20 V vs. SCE) and 4‐picolyl esters ( E red =−2.62 V vs. SCE) were reduced by N ‐alkylation of the heterocycle ( N ‐methyl‐4‐picolinium: E red =−1.10 V vs. SCE), and also by adding electron‐withdrawing groups to the pyridinium ring (2‐cyano‐picolinium esters E red ≈−0.50 V vs. SCE) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The corresponding reduced radicals of the acceptor units, Pyr À and NB À , are not detected in the spectrum since their absorption bands (for Pyr À at 410 nm, 25 for NB À at 437 and 431 nm (ref. 26)) are out of the spectral range of detection of the pump and probe apparatus used.…”
Section: View Article Onlinementioning
confidence: 99%
“…It was also reported that the 4-picolyl groups were deprotected by a light-absorbing photosensitizer. 7 An excellent yield for the free carboxylate has been obtained using visible-lightabsorbing citrate-stabilized metal complexes to mediate electron transfer between dithiothreitol and an N-methylpicolinium ester in aqueous solution by Falvey's group. 8 Our continued interest in peptide synthesis recently prompted us to explore the efficient deprotection of 4-picolyl esters.…”
mentioning
confidence: 99%